DIMENSI OLAHRAGA PENDIDIKAN DALAM PELAKSANAAN PENJASORKES DI SEKOLAH - Uket; Cukei (Pendidikan Jasmani, Kesehatan, dan Rekreasi, 2021)
Sports Education carried out with the purpose of education through all movement activities that are directed to meet the needs and goals of education itself. Sports education idenitik with physical education activity, sport and health are implemented at every level of education, or better known as Penjasorkes. There are three dimensions of sport education in schools in the implementation Penjasorkes, that is physical education, health education and sports education. The implications of the implementation of Sport Education is expected that students have physical fitness, enjoyment in physical activity and sport, forming healthy man physically and has a strong character and smart as a nation of Indonesia.